2020
DOI: 10.2147/opth.s236825
|View full text |Cite
|
Sign up to set email alerts
|

<p>Finite Element Analysis of Air Gun Impact on Post-Keratoplasty Eye</p>

Abstract: Due to the mechanical vulnerability of eyes that have undergone penetrating keratoplasty (PKP), it is clinically important to evaluate the possibility of corneal wound dehiscence by blunt impact. We have previously developed a simulation model resembling a human eye based on information obtained from cadaver eyes and applied three-dimensional finite element analysis (FEA) to determine the physical and mechanical response to an air gun impact at various velocities on the post-PKP eye. Methods: Simulations in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“… 32 Vitreous was modeled as a solid mass with a hydrostatic pressure of 20 mmHg (2.7 kPa). 37 , 38 To our knowledge, there are no published data on the mechanical properties, especially on the tensile strength, of the zonule of Zinn, and thus, the suspensory ligaments and ciliary muscles are not included in this model. The elastic properties and meshing principles of the model human normal eye (emmetropia) were similar to those in previous reports.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 32 Vitreous was modeled as a solid mass with a hydrostatic pressure of 20 mmHg (2.7 kPa). 37 , 38 To our knowledge, there are no published data on the mechanical properties, especially on the tensile strength, of the zonule of Zinn, and thus, the suspensory ligaments and ciliary muscles are not included in this model. The elastic properties and meshing principles of the model human normal eye (emmetropia) were similar to those in previous reports.…”
Section: Methodsmentioning
confidence: 99%
“…32 This model human eye was also used in our studies on airbag impact in various situations. [33][34][35][36][37][38] We applied this FEA model and reported that considerable damage was observed especially at higher impact velocities, such as 50 or 60 m/s, in eyes with any axial length, and deformation was most evident in the anterior segment. 39 In these studies, we mainly reported mechanical damage of the ocular surface, such as laceration, perforation, etc., and deformation of the whole eyeball was evaluated, but intraocular deformation, which is closely related to angle recession, lens rupture and vitreous traction etc., was not evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…22 We have previously developed a simulation model resembling a human eye 23 and applied three-dimensional FEA to determine the physical and mechanical response of the eyeball to an impacting airbag or airsoft gun projectile. [24][25][26][27][28][29][30] The important benefits of computer models to analyze biomechanical experiments and to quantify mechanical parameters are that we can evaluate the tensile strain of ocular segments by freely changing the impacting velocity or ocular tissue properties and they may reduce the need for animal studies, which are being increasingly restricted on ethical grounds.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we planned to study the kinetic phenomenon of an airbag impact on a human eye using a FEA method, which was also applied in several of our previous studies on other types of injury than airbag injury [ 23 , 24 ]. If we were able to reproduce the kinetic phenomena including intraocular deformation caused by an airbag impact sequentially, this would increase understanding of the pathophysiological mechanism of blunt ocular trauma by an airbag.…”
Section: Introductionmentioning
confidence: 99%